Inorganic fouling of an anaerobic membrane bioreactor treating leachate from the organic fraction of municipal solid waste (OFMSW) and a polishing aerobic membrane bioreactor. (March 2016) - Trzcinski, Antoine P.; Stuckey, David C.
Highlights: Landfill leachate was treated in a Submerged Anaerobic Membrane BioReactor. More than 90% COD removal was obtained at an HRT of 0.4–0.6 days. Monohydrocalcite precipitated on the membrane causing flux drop. Hydroxyapatite precipitated in the aerobic polishing step. Abstract: The treatment of leachate (Average TCOD = 11.97 g/L, 14.4% soluble) from the organic fraction of municipal solid waste was investigated using a Submerged Anaerobic Membrane BioReactor (SAMBR), followed by an aerobic membrane bioreactor (AMBR) to polish this effluent. This paper investigated the exact nature and composition of the inorganic precipitate in each of the reactors in the process. The flux decreased due to precipitation of calcium as monohydrocalcite (CaCO3 ·H2 O) containing traces of metals onto the SAMBR membrane because of high CO2 partial pressures. Precipitation of calcium in the AMBR was also observed due to a higher pH. In this case, phosphorus also precipitated with calcium in two different phases: the background layer contained calcium, oxygen, carbon and small amounts of phosphorus (2–6.7%), while flakes containing calcium, oxygen and higher amounts of phosphorus (10–17%) were probably hydroxyapatite (Ca5 (PO4 )3 OH).